La rédaction tardive des récits de transfuge de classe : une problématique du vieillissement social - David Vrydaghs (Contextes)
Taking as its starting point the observation that many class defector narratives were written when their authors were already of a certain age—often in their fifties—this article first examines the reasons these authors themselves give for writing so late in life. It then reframes the initial question in terms of social ageing. The article goes on to trace the gradual ageing of the genre itself—specifically, its institutionalization in two distinct fields, the academic and the literary—through a slow and fragile process during which this narrative form has had to compete with more established ones: ego-histories on the one hand, and narratives of filiation on the other. This social ageing of the class defector narrative also helps explain the advanced age of its authors